A decline in planned, but not spontaneous, preterm birth rates in a large Australian tertiary maternity centre during COVID‐19 mitigation measures. (12th July 2021) - Gallo, Linda A.; Gallo, Tania F.; Borg, Danielle J.; Moritz, Karen M.; Clifton, Vicki L.; Kumar, Sailesh
Abstract : Background: Reports from around the world suggest that rates of preterm birth decreased during COVID‐19 lockdown measures. Aims: To compare the prevalence of preterm birth and stillbirth rates during COVID‐19 restriction measures with infants born at the same maternity centre during the same weeks in 2013–2019. Materials and Methods: Deidentified data were extracted from the Mater Mothers' healthcare records database. This is a supra‐regional tertiary perinatal centre. Logistic regressions were used to examine singleton live preterm birth rates during the beginning of COVID‐19 restrictions (16 March‐17 April; 'early'; 6955 births) and during the strictest part of COVID‐19 restrictions (30 March‐1 May; 'late'; 6953 births), according to gestational age subgroups and birth onset (planned or spontaneous). We adjusted for multiple covariates, including maternal age, body mass index, ethnicity, parity, socioeconomic status, maternal asthma, diabetes mellitus and/or hypertensive disorder. Singleton stillbirth rates were also examined between 16 March–1 May. Results: Planned moderate/late preterm births declined by more than half during early COVID‐19 restrictions compared with the previous seven years (29 vs an average of 64 per 1000 births; adjusted odds ratio 0.39, 95% CI 0.22–0.71). There was no effect on extremely or very preterm infants, spontaneous preterm births, or stillbirth rates. Rolling averages from January to June revealed a two‐week non‐significant spike in spontaneous preterm births from late April to early May, 2020. Conclusions: Together with evidence from other nations, the pandemic provides a unique opportunity to identify causal and preventative factors for preterm birth.